Human Sensory LTP Predicts Memory Performance and Is Modulated by the BDNF Val66Met Polymorphism - Spriggs, Meg J.; Thompson, Chris S.; Moreau, David; McNair, Nicolas A.; Wu, C. Carolyn; Lamb, Yvette N.; McKay, Nicole S.; King, Rohan O. C.; Antia, Ushtana; Shelling, Andrew N.; Hamm, Jeff P.; Teyler, Timothy J.; et al. (Frontiers in Human Neuroscience, 2019)
Background: Long-term potentiation (LTP) is recognised as a core neuronal process underlying long-term memory. However, a direct relationship between LTP and human memory performance is yet to be demonstrated. The first aim of the current study was thus to assess the relationship between LTP and human long-term memory performance. With this also comes an opportunity to explore factors thought to mediate the relationship between LTP and long-term memory. The second aim of the current study was to explore the relationship between LTP and memory in groups differing with respect to brain-derived neurotrophic factor (BDNF) Val66Met; a single-nucleotide polymorphism (SNP) implicated in memory function. Methods: Participants were split into three genotype groups (Val/Val, Val/Met, Met/Met) and were presented with both an EEG paradigm for inducing LTP-like enhancements of the visually-evoked response, and a test of visual memory. Results: The magnitude of LTP 40 min after induction was predictive of long-term memory performance. Additionally, the BDNF Met allele was associated with both reduced LTP and reduced memory performance. Conclusions: The current study not only presents the first evidence for a relationship between sensory LTP and human memory performance, but also demonstrates how targeting this relationship can provide insight into factors implicated in variation in human memory performance. It is anticipated that this will be of utility to future clinical studies of disrupted memory function.